Some trace element contents of the common basement rocks of the Safaga Region, Eastern Desert - Gindy Amin R.; Khalil Sobhy O.; Dabous Adel A. A. (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1976)
Fourteen samples from the common igneous types forming the basement in the Safaga area were analysed by emission spectrography and neutron activation techniques and their contents in the following 22 trace elements were determined: B, Ba, Be, Co, Cr, Cs, Cu, Hf, La, Ni, Pb, Rb, Sc, Sm, Sr, Ta, Th, U, V, Y, Yb and Zr. The results obtained are discussed and compared with those of the corresponding world's averages. All the Safaga basement rocks are apparently geochemically strongly impoverished in boron, rather impoverished in copper and lead but somewhat enriched in nickel, cobalt, and yttrium. The granitic rocks are also rather impoverished in vanadium but rather richer in barium, strontium, hafnium and beryllium than the corresponding world's averages.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok